Speed-adaptive vertical handoff algorithm based on fuzzy logic in vehicular heterogeneous networks - Ma, Bin; Liao, Xiaofeng (2012 9th International Conference on Fuzzy Systems and Knowledge Discovery, 2012)
This paper proposes a multi-mode vehicle terminal based speed adaptive vertical handoff policy in vehicular heterogeneous networks. The proposed vertical handoff algorithm uses speed adaptive policy in the network discovery phase, which overcomes the drawbacks of the fixed, single network discovery methods by using RSS, raises candidate network sets update rate and improves the network discovery time of high-speed mobile terminals. Moreover, a handoff decision algorithm based on type-2 fuzzy logic is proposed, which takes into account a variety of access network and user properties, selects the network with the maximum satisfaction value as the best handoff network. Simulation results show that the proposed algorithm can effectively improve the network update speed, lower network blocking probability, and assure the effectiveness and fairness of handoff compared with traditional vertical handoff based on type-1 fuzzy logic algorithm.